Efektivitas Pembelajaran Daring Terhadap Perilaku Belajar Siswa Pada Mata Pelajaran Matematika Di Kelas Iii Sd Negeri 91 Kendari - Epa Jasman (Prodi PGSD Unsultra, 2021)
The emergence of the Covid-19 pandemic has necessitated the implementation of online learning, which has undoubtedly affected students’ learning behavior, including those in elementary schools. As a new learning process, it is important to study the effectiveness of online learning activities. This study aims to determine the effectiveness of online learning and to analyze the learning behavior of third-grade students at SD Negeri 91 Kendari. Data collection was carried out from July to August 2021. The primary data sources of this research were observations, questionnaires, and interviews related to the effectiveness of online learning and student learning behavior. The analysis results showed that the effectiveness level of online learning during the Covid-19 pandemic on students’ learning behavior at SD Negeri 91 Kendari still needs improvement, as it remains below the “moderate” category. This means that in conducting online learning, teachers still need to enhance their efforts to improve the quality of online learning.